THE ROLE OF ARTISTIC LITERATURE IN THE SPIRITUAL AND MORAL EDUCATION OF CHILDREN - Faizullayeva, M.Z. (Journal of Higher Education and Academic Advancement, 2024)
In the spiritual and moral education of children of preschool age in our country the wide use of fiction shows an effective result. The task of the pedagogue is to educate children spiritually and morally by awakening their interest in fiction and listening to it. It forms qualities such as striving for goodness, valuing friendship, bravery, bravery and bravery in children.